Evaluación de harina de sangre bovina en la alimentación de cerdos en la etapa de crecimiento y engorde - Laso Milán, Carmen Amelia (2017)
In the pig breeding program of the faculty of Agricultural Sciences of the Bolívar State University in the Guaranda district, Bolívar Province, the effect of bloodmeal added to commercial concentrated feed for store pigs in the following percentages: 5, 8 and 11 was studied on 24 Landrace pigs (12 male and 12 female) beginning at the age of 65 days and an average weight of 19.46 kg. Those pigs were distributed using a block design at total random. The results of the experiment showed significant and highly significant differences during the growth and finishing period confirming that the added bloodmeal increased productivity, generating higher incomes to the pig breeder due to the increased weight and obtaining efficient feed conversions. On the base of these results we can recommend the addition of 5% of bloodmeal to the original feed since this results in final weight of 90 kg in female and 81.67 kg in male pigs per average. As to hematological alterations of the pigs stress formules without infectious or inflammatory problems were observed. With regard to the cost-benefit ratio it was determined that the best profitability was reached adding 5% (corresponding to the T2 test group) of bloodmeal to the feed, obtaining a benefit of $ 0.12 for each dollar invested. Key words: Bloodmeal, protein, digestibility, palatability, additive, midlings, origina weight, weekly weight gain, monthly weight gain, feed conversion ratio, final weight, hematology, cost-benefit.